Pengaruh Kepemimpinan dan Iklim Organisasi terhadap Quality of Work Life serta Implikasinya terhadap Kepuasan Kerja (Studi Kasus pada PT Mediatama Binakreasi) - Arief Budiman (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The research explain the relationships and the influence of several variables that have been defined. Data analysis techniques using Structural Equation Modeling (SEM) to describe the relationship with the latent variable indicators (measurement model) and to describe relationships between variables latent (structural model). Distributing questionnaires conducted with stratified random sampling method. A population of 259 respondents with a defined sample 157 respondents. The results of the analysis of this data showed that, overall test model fit was acceptable, seen from the leadership variables significantly influence the quality of work life, variable organizational climate significantly influence the quality of work life, leadership variables significantly influence job satisfaction, variable organizational climate significantly influence job satisfaction, and the variable quality of work life significant effect on job satisfaction. Thus, we can conclude organizational climate had a dominant influence on job satisfaction, this shows that the climate is a good organizational climate that gives a sense of comfort for employees to perform work activities, which in turn have a positive influence on the performance it achieves.